Synthesis and Characterization of Nickel Zinc Ferrite Nanoparticles - K. Hedayati (Journal of Nanostructures, 2015)
In this research nickel zinc ferrite nanoparticles with composition of Ni1-xZnxFe2O4 (where x=0, 0.3, 0.7, 1) were synthesized by a sol-gel method at 600 °C for 5 hours. The structure of nanoparticles was studied using X-ray diffraction pattern. The lattice parameter of ferrite nanoparticles was calculated and indicates lattice constant of nanoparticles depend on zinc concentration. The crystallite size of nickel zinc nanoparticles was calculated by Debye–Scherrer equation and the crystallite sizes of nanoparticles decreased by increasing in x contents. Morphology of nanoparticles was observed and investigated using the scanning electron microscopy. The grain size of nickel zinc ferrite nanoparticles were in suitable agreement with the crystalline size calculated by X-ray diffraction results. Magnetic properties of nanoparticles were examined with vibration sample magnetometer. Hysteresis loops of nanoparticles reveal the super-paramagnetic behavior.